Diagnostico de los sistemas de producción en la cuenca alta del rio cumbaza-San Martín-Perú - Baca Saavedra, Graciela Romualda (2000)
Presently work of investigation titled "Diagnosis of the Practiced Systems of Production for the Farmers from the High Cuenca of the river Cumbaza", the design was used totally at random with 10 observations (farmers) for community, m parcels of the families of farmers seated in the communities of Aviación, Chiricyacu, San Roque (County of you Lick) and San Antonio (County of San Martín). The objectives were: to characterize the systems of agricultura! production and to define the main restrictive factors of the agricultura! production. They took into account ecological aspects, climate (PP°, T', altitude), area of life, vegetation, organic matter, slope, rocky blooming, cultivations (annual, semiperennes, perennial), socio-economic (population, level of life, services, yiclds and financia! analysis. The conclusions were: The native communities of Aviación and Chiricyacu develop a system agroforestal of 80 and 90 respectively low% the diversified modality and disordcrcd with a grcat varicty of associatc and inscrtcd spccics, without earth movement neither the agroqufmicos use being translated this way to a bigger accumulation of organic matter of high level and biomass for area unit prcscrving thc floors and thc ccosystcm. However in the mestizo communities of San Roque (50%) and San Antonio (60%) the monocultivo prevails this system evidently it is a restrictive factor from thc cconomic point of vicw, bcing a dcmanding systcm, togcthcr to thc topography of the floor (high slopes, rocky blooming, organic matter, sour floors, shortage of earth of agricultural aptitude) and the clima te, they favor the loss of agricultural floor for erosion impacting in the production and productivity of the cultivations.